Interpersonal Realizations in the 'Panjat Pinang' Comic of English for Nusantara Grade 8 - Nabila Alqoyyumi; Nina Puspitaloka; Acep Bahrum Kamil (Universitas Islam Negeri Palopo, 2026)
This study investigates the realization of interpersonal meaning through mood types and modality in the “Panjat Pinang” comic from the English for Nusantara Grade 8 textbook. It addresses the limited focus on textbook-based SFL analysis and the lack of attention to interpersonal metafunction in educational comics within the Indonesian EFL context. Grounded in Halliday and Matthiessen’s interpersonal metafunction theory, this descriptive qualitative study analyzes verbal dialogues in the comic, using the clause as the unit of analysis to identify mood types—declarative, interrogative, imperative, and exclamative—as well as modality expressions. The findings reveal that declarative clauses dominate the discourse, functioning not only to convey information but also to construct cultural narratives and identity. Interrogative clauses facilitate interaction and engagement, while imperative and exclamative forms contribute to politeness and emotional expression. Although modality appears in limited instances, it plays a significant role in expressing interpersonal stance, particularly in representing values such as humility, certainty, and politeness. In addition, the study highlights that interpersonal meaning is constructed through the interaction of verbal and visual elements, reinforcing the multimodal nature of the comic. These findings demonstrate that the “Panjat Pinang” comic functions as a multimodal pedagogical resource that models authentic interpersonal communication. This study contributes to SFL research by providing empirical evidence of interpersonal meaning in a textbook-based comic, and to EFL material development by showing how culturally embedded comics can support learners’ communicative and pragmatic competence.